"When You Come Together and Do Everything, It'll be Better for Everybody": Exploring Gender Relations Among Two Southeastern Native American Tribes. (August 2022) - Lilly, Jenn; McKinley, Catherine E.; Knipp, Hannah; Liddell, Jessica L.
Prior to the imposition of patriarchal colonial norms, Native American (NA) gender relations were characterized as complementary and egalitarian; however, little research has explored gender relations within NA communities today. This study used a community-based critical ethnography to explore contemporary NA gender relations with a purposive sample of 208 individuals from the "Coastal Tribe" and 228 participants from the "Inland Tribe." After participant observation, interviews, and focus groups were conducted, a collaborative approach to reconstructive analysis was used to identify themes in the data. Within these communities, gender relations tended to reflect egalitarian and cooperative but gendered norms, and participants provided examples of how tribal members are transcending patriarchal colonialism. Through the lens of the Framework of Historical Oppression, Resilience, and Transcendence, we theorize how these gender norms may protect families from risks associated with historical oppression and promote family resilience with implications for research, practice, and policy.